2017
DOI: 10.1111/joic.12362
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Elderly Patients With Severely Calcified Coronary Lesions Undergoing Orbital Atherectomy

Abstract: The elderly represented a sizeable number of patients who underwent orbital atherectomy. It is a safe and effective treatment strategy for elderly patients with severe CAC as the clinical outcomes were similar to their younger counterparts. A randomized trial should further clarify the role of orbital atherectomy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…al. reports their results in elderly patients (>75 years of age) versus non‐elderly and found no difference in angiographic or clinical complications between the two groups . These data suggest that appropriately selected, high risk elderly patients may be safely treated with atherectomy.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…al. reports their results in elderly patients (>75 years of age) versus non‐elderly and found no difference in angiographic or clinical complications between the two groups . These data suggest that appropriately selected, high risk elderly patients may be safely treated with atherectomy.…”
mentioning
confidence: 91%
“…These four new studies published in the Journal suggest combined therapy with atherectomy and DES or DCB is safe and effective in the management of calcified lesions.…”
mentioning
confidence: 99%
“…The use of orbital atherectomy has been found to be safe and effective in a multicenter registry previously, and new studies have since demonstrated safety in high risk elderly patients . These results offer safe and effective management of calcified lesions with combined approach with atherectomy followed by DES or DCB.…”
Section: Calcified Coronariesmentioning
confidence: 88%
“…[42] At 1-year follow-up, the composite rate of major adverse cardiac and cerebrovascular events occurred in 12.6%, with 4.0% all-cause mortality, 1.8% MI rate and TVR rate of 7.5%. [43]…”
Section: Orbital Atherectomymentioning
confidence: 99%